Analyzing The Impact Of Employee Competence, Organizational Climate, and Physical Work Environment On Worker Productivity in Palm Oil Manufacturing - Sitorus, Ezekiel Berliantoro; Panjaitan, Maludin; Purba, Jon Henri; Sinaga, Kristin (Equivalent : Journal of Economic, Accounting and Management, 2025)
This study examines the influence of employee competence, organisational climate, and work environment on work performance at PT Perkebunan Nusantara IV Pasir Mandoge Palm Oil Factory. A quantitative method with an associative design was employed, involving 120 employees selected from a population of 172 using the Slovin formula with a 5% margin of error. Data were collected through five‑point Likert scale questionnaires and analysed using multiple linear regression with standard classical assumption tests in IBM SPSS Statistics. The results indicate that employee competence, organisational climate, and work environment each have positive and significant partial effects on work performance, with t‑values of 2.276, 3.213, and 3.787, respectively, all exceeding the critical value of 1.980. Simultaneously, these three variables significantly affect work performance, as shown by an F‑statistic of 9.934, greater than the critical value of 2.68. The coefficient of determination (R‑square) of 0.204 shows that 20.4% of the variation in work performance is explained by these variables, while 79.6% is attributed to other factors. The findings highlight that the work environment has the strongest association with work performance, underscoring the importance of supportive organisational conditions to enhance employee productivity and engagement.